Heiligsprechung und Selbstkritik: Plädoyer für ein angemessenes Gedenken an Edith Stein - Siegele-Wenschkewitz, Leonore (Kirchliche Zeitgeschichte, 2000)
Fifty years after her death, Edith Stein still remains a controversial figure. The official Catholic Church sees her as a Christian martyr. But the Jewish community takes the view that she was murdered because of her racial origin, not her Christian faith. Any appropriate commemoration has surely to take critical note of the fact that neither theology nor the church was able to prevent, or even to oppose, the kind of racial fanaticism and violent persecution by the Nazis of the Jews which led to her death. Any biographical study of this one victim has to take into account the church's failure in this affair. Edith Stein, we know, opposed the prevailing type of thinking about Judaism of her day. Instead she sought to raise the consciousness of the connections and the similarities between Christianity and Judaism. On the other hand, we do have some of her statements which reflect a more traditionally negative view of the future of Judaism. How to combine the prophetic aspects of her attempts at reconciliatory understanding with the more pejorative aspects of her theological ideas caught in their contemporary limitations, poses problems. But both have to be included in any comprehensive and fair account of her life as a Catholic Christian and a member of the Jewish people.